2014
DOI: 10.1016/j.jfluchem.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

A (Fluoroalkyl)Guanidine Modulates the Relaxivity of a Phosphonate-Containing T 1 -Shortening Contrast Agent

Abstract: Responsive magnetic resonance imaging (MRI) contrast agents, those that change their relaxivity according to environmental stimuli, have promise as next generation imaging probes in medicine. While several of these are known based on covalent modification of the contrast agents, fewer are known based on controlling non-covalent interactions. We demonstrate here accentuated relaxivity of a T1-shortening contrast agent, Gd-DOTP5− based on non-covalent, hydrogen bonding of Gd-DOTP5− with a novel fluorous amphiphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…(6) The T 1 of these protons is then short, owing to their proximity to the paramagnetic Gd 3+ ion. Exchange of these protons across sites on polymers, chelates and whatever water molecules are present in the aggregate facilitate proton movement to the shell interior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(6) The T 1 of these protons is then short, owing to their proximity to the paramagnetic Gd 3+ ion. Exchange of these protons across sites on polymers, chelates and whatever water molecules are present in the aggregate facilitate proton movement to the shell interior.…”
Section: Resultsmentioning
confidence: 99%
“…Inside the NAC the second 'hydration sphere' is probably replaced by protons from the PAH amino groups that hydrogen bond to the chelate, forming the aggregate (6). The T 1 of these protons is then short, owing to their proximity to the paramagnetic Gd 3+ ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Therefore, understanding the coordination chemistry of Gd III and other trivalent lanthanide ions is critical to the design of new contrast agents because the coordination of these ions impacts their ability to alter contrast and also changes their properties with respect to biodistribution and toxicity. We have explored trivalent ions as contrast agents, 28 but recently have focused a great deal of effort into divalent europium as a contrast agent.…”
Section: Contrast Agents From Divalent Europiummentioning
confidence: 99%
“…However, fluorinated compounds can have relatively long relaxation times, resulting in long acquisition times [32]. This problem can be circumvented by introducing in the structure of the 19 F CA paramagnetic centers, such as Gd(III) in the proximity of 19 F nuclei, shortening T1 and allowing for the acquisition of a larger number of scans in the same experimental time [33,34,35,36]. In this context, Yu and coworkers reported that in a small, water soluble compound having nine equivalent fluorine atoms which is able to chelate gadolinium ions [37] the T1 shortening enabled by the paramagnetic center significantly improved the signal to noise ratio.…”
Section: Introductionmentioning
confidence: 99%